2021
DOI: 10.1186/s40069-021-00455-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Basic Mechanical Properties of Core-Column Non-mortar Aerated Concrete Block Masonry

Abstract: Autoclaved aerated concrete (AAC) block masonry has been widely used for bearing walls of multi-story buildings or non-bearing walls of high-rise buildings because of its unique advantages, such as lightweight, low pollution output, and excellent thermal insulation performance. However, traditional AAC block masonry has the disadvantages of high water absorption, poor adhesion to mortar, and low construction efficiency. In order to improve the performance of traditional AAC masonry, this paper proposed a new k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…More study is needed to improve the bond strength between bamboo and concrete. Tianxiang Pi et al (2021) [26] conducted experimental and analytical research on corecolumn non-mortar aerated concrete block masonry was reported which described at the construction methods and mechanical characteristics. The study was divided into four sections: (a) masonry construction technique; (b) masonry compressive strength, deformation performance, and compression mechanism; (c) masonry shear strength and shear mechanism; (d) numerical simulation analysis of compression and shear specimens Li, F., Chen et al ( 2021) [27] explored Fundamental Properties and Thermal Transferability of Masonry Built by Autoclaved Aerated Concrete Self-Insulation Blocks With a compressive strength of 4.0 MPa and a dry density of 558 kg/m3, the best products of the AAC self-insulation block were created.…”
Section: Bose Andmentioning
confidence: 99%
“…More study is needed to improve the bond strength between bamboo and concrete. Tianxiang Pi et al (2021) [26] conducted experimental and analytical research on corecolumn non-mortar aerated concrete block masonry was reported which described at the construction methods and mechanical characteristics. The study was divided into four sections: (a) masonry construction technique; (b) masonry compressive strength, deformation performance, and compression mechanism; (c) masonry shear strength and shear mechanism; (d) numerical simulation analysis of compression and shear specimens Li, F., Chen et al ( 2021) [27] explored Fundamental Properties and Thermal Transferability of Masonry Built by Autoclaved Aerated Concrete Self-Insulation Blocks With a compressive strength of 4.0 MPa and a dry density of 558 kg/m3, the best products of the AAC self-insulation block were created.…”
Section: Bose Andmentioning
confidence: 99%